Facial Paralysis in Children - Reddy, Sashank; Redett, Richard (Facial Plastic Surgery, 2015)
Facial paralysis can have devastating physical and psychosocial consequences. These are particularly severe in children in whom loss of emotional expressiveness can impair social development and integration. The etiologies of facial paralysis, prospects for spontaneous recovery, and functions requiring restoration differ in children as compared with adults. Here we review contemporary management of facial paralysis with a focus on special considerations for pediatric patients.
Keywords: facial paralysis; pediatrics; facial nerve